Response of Photosynthesis to High Growth Temperature Was Not Related to Leaf Anatomy Plasticity in Rice (Oryza sativa L.) - Yang, Desheng; Peng, Shaobing; Wang, Fei (Frontiers in Plant Science, 2020)
Photosynthesis is highly sensitive to high temperature stress, and with the rising global temperature, it is meaningful to investigate the response of photosynthesis to growth temperature and its relationship with leaf anatomy plasticity. We planted 21 cultivars including eight indica cultivars, eight japonica cultivars, and five javanica cultivars in pot experiments under high growth temperature (HT, 38/28°C, day/night) and control treatment (CK, 30/28°C, day/night). Photosynthetic rate (A), stomatal conductance (gs), transpiration rate (E), stomatal density (SD), vein density (VD), minor vein area (SVA), and major vein area (LVA) were measured after 30 treatment days. Results showed HT significantly increased A, gs, and E, while significantly decreased SD and LVA. There was no significant difference in A among the three subspecies both under CK and HT, while the javanica subspecies had higher gs, E, SVA, and LVA under HT, and the indica cultivars had higher VD and SD both under CK and HT. The javanica subspecies had higher relative value (HT/CK) of A, gs, and E, while difference was not observed in the relative value of SD, VD, and LVA among the three subspecies. The relative value of A was positively related to that of gs, while the latter was not correlated with the relative value of SD, VD, SVA, and LVA. Overall, the results suggested the increase of A and gs at HT was not attributed to leaf anatomy plasticity in respect of stomata and vein under HT.